La prison de Guingamp, de l’ombre à la lumière - Emmanuel Laot (Criminocorpus)
Born of European and American influences, at the heart of the French prison reform that imposed the solitary confinement regime in France, the prison of Guingamp is a unique architectural testimony of French and European penitentiary history. The prison was built by the Côtes-du-Nord department and opened in 1841 thanks to Charles Lucas, general inspector of prisons, Louis Lorin, departmental architect and Alexis de Tocqueville, the great French historian, thinker and publicist. We owe them this humanist architectural design of the idea that a prison is not simply a place of confinement. Closed for the first time in 1934, it took in Spanish refugees in 1937 and 1939, then reopened in 1941 and was disused in 1952. It locked up 31,661 people. Sold by the Department to the Government, it was used as a place for tax archival storage and even housing. Without any maintenance, it deteriorated heavily, victim of storms and fires. Purchased in 1992 by the municipality of Guingamp, then listed in the supplementary inventory of historical monuments, the process led to the classification of the former prison and its walls in 1997. After several stages of conservation work, which began in 2008, and then rehabilitation and reallocation from 2013 onwards with a view to a very ambitious artistic and cultural project, accessible to the public, it will house the GwinZegal Photographic Art Centre in 2019 and the National Higher Institute for Artistic and Cultural Education in 2021.